Sosialisasi CALL Berbasis Mesin Penerjemah Online Untuk Meningkatkan Keterampilan Menulis Bagi Mahasiswa - Arda Adianto; Eva Sulistiana (CV. Multi Kreasi Media, 2025)
The integration of technology in foreign language learning has become essential in higher education. However, students often rely on online translation tools without proper verification, resulting in inaccurate language production. This community service program aimed to enhance students’ understanding and skills in utilizing online translation tools as Computer Assisted Language Learning (CALL) at Universitas Hafshawaty Zainul Hasan (UNHASA). The program employed preparation, implementation through interactive training, and evaluation stages. Conducted on June 17, 2025, the activity involved 27 students from various study programs. The results indicated improved conceptual understanding of translation tools, enhanced English writing skills, and increased learner autonomy and confidence. Evaluation results revealed that 92% of participants found the program highly beneficial and 88% intended to apply the acquired knowledge in their learning activities. This program contributes to strengthening students’ digital literacy and serves as a sustainable model for technology integration in language learning.